Therapeutic hypothermia for acute ischaemic stroke. Results of a European multicentre, randomised, phase III clinical trial. (September 2019) - van der Worp, H Bart; Macleod, Malcolm R; Bath, Philip MW; Bathula, Raj; Christensen, Hanne; Colam, Bridget; Cordonnier, Charlotte; Demotes-Mainard, Jacques; Durand-Zaleski, Isabelle; Gluud, Christian; Jakobsen, Janus Christian; Kallmünzer, Bernd; et al.
Abstract: Introduction: We assessed whether modest systemic cooling started within 6 hours of symptom onset improves functional outcome at three months in awake patients with acute ischaemic stroke. Patients and methods: In this European randomised open-label clinical trial with blinded outcome assessment, adult patients with acute ischaemic stroke were randomised to cooling to a target body temperature of 34.0–35.0°C, started within 6 h after stroke onset and maintained for 12 or 24 h, versus standard treatment. The primary outcome was the score on the modified Rankin Scale at 91 days, as analysed with ordinal logistic regression. Results: The trial was stopped after inclusion of 98 of the originally intended 1500 patients because of slow recruitment and cessation of funding. Forty-nine patients were randomised to hypothermia versus 49 to standard treatment. Four patients were lost to follow-up. Of patients randomised to hypothermia, 15 (31%) achieved the predefined cooling targets. The primary outcome did not differ between the groups (odds ratio for good outcome, 1.01; 95% confidence interval, 0.48–2.13; p = 0.97). The number of patients with one or more serious adverse events did not differ between groups (relative risk, 1.22; 95% confidence interval, 0.65–1.94; p = 0.52). Discussion: In this trial, cooling to a target of 34.0–35.0°C and maintaining this for 12 or 24 h was not feasible in the majority of patients. The final sample was underpowered to detect clinically relevant differences in outcomes. Conclusion: Before new trials are launched, the feasibility of cooling needs to be improved.